A new species of Sycorax Curtis (Diptera, Psychodidae, Sycoracinae) collected on harlequin frogs (Anura: Bufonidae, Atelopus) in the Ecuadorian Andes - Bravo, Freddy; Salazar-Valenzuela, David (Zootaxa, 2009)
Sycorax wampukrum sp. nov. is described from the Amazonian slopes of the Cordillera Oriental of southern Ecuadorian Andes. This new species constitutes the first record of the genus from Ecuador. Males and females of this new species were found in contact with the dorsal surfaces of head, body and extremities of male individuals of harlequin frogs, thus establishing the second record of species of the genus Sycorax feeding on frog blood.